Water constraints drive allometric patterns in the body shape of tree frogs - Kathleen M. S. A. Castro (Nature Portfolio, 2021)
Abstract The origin of morphological diversity is a critical question in evolutionary biology. Interactions between the environment and developmental processes have determining roles in morphological diversity, creating patterns through space and over time. Also, the shape of organisms tends to vary with increasing size as a result of those developmental processes, known as allometry. Several studies have demonstrated that the body sizes of anurans are associated with hydric conditions in their environments and that localities with high water stress tend to select for larger individuals. However, how environmental conditions alter those patterns of covariance between size and shape is still elusive. We used 3D geometric morphometric analyses, associated with phylogenetic comparative methods, to determine if the morphological variations and allometric patterns found in Arboranae (Anura) is linked to water conservation mechanisms. We found effects of the hydric stress on the shape of Arboranae species, favouring globular shapes. Also, the allometric patterns varied in intensity according to the water stress gradient, being particularly relevant for smaller frogs, and more intense in environments with higher water deficits. Our study provides empirical evidence that more spherical body shapes, especially among smaller species, reflect an important adaptation of anurans to water conservation in water-constrained environments.